Bahasa Inggris - Makruf Widodo; Drajat Stiawan (Jurnal Penelitian, 2021)
The Neighborhood/Syuran tradition is not a mere socio-cultural phenomenon, but there is a deep philosophical meaning behind this annual event. The Banyumudal Panjer Kebumen Environmental Tradition places culture and local wisdom as the locus of faith in communicating with God. So that the actualization of culture is created that not only reflects syncretism and aculturalism but is also full of sacredness and nuances of Islam and faith. The encounter between Islamic values and local culture is evidence of a reception between religion and culture. This study aims to determine the process and results of the interaction between the teachings in the Qur'an and the culture of the Banyumudal Panjer Kebumen Society. This study uses a field research method, using Malinowski's theory of functionalism. Through this theory, researchers can uncover and examine more deeply the meaning and function of Syuran rituals. The results of this study show that 1) there are four forms of reception of the Qur'an in the environment/Syuran culture: symbolic receptions, historical receptions, aesthetic receptions and exegesis receptions. 2) Environment/Syuran is a socio-religious phenomenon that combines three important elements, namely religion, culture and economy. The integration of these three elements is represented by three important symbols of civilization for the people of Banyumudal, namely the triangle formed between the Environment/Syuran as a culture, the Banyumudal Mosque as a religious center and slaughtering chickens as part of the community's economy.